Zjawisko pokusy nadużycia i jego rola podczas kryzysu azjatyckiego w 1997 roku - Mazurek, Szymon (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Moral hazard refers to the belief that banks and large companies are effectively guaranteed by their governments and can be lent to at government rather than private risk. This mechanism played an essential role during financial crisis in Asia in 1997. Moral hazard, which causes irrational investment decisions, leads to the financial bubble burst, making the economy highly vulnerable to self-fulfilling crisis. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 235-246